Memahami Peluang Dan Risiko Investasi Terhadap Masyarakat Dukuh Pakis Surabaya - Vaneza Sabatimy; Dhani Ichsanuddin Nur (Institut Nalanda, 2023)
Investment trading is a financial activity that is increasingly popular in this modern era. It involves buying and selling financial instruments such as stocks, bonds, commodities, and currencies with the aim of making a profit. One form of investment is trading. Before that, it is necessary to have a good understanding of investment through investment trading education. Firstly, investment trading education includes a basic understanding of the financial market, including trading mechanisms, types of traded assets, and available financial instruments. However, it also involves risks, and success in investment trading requires a good understanding of the market, thorough analysis, and effective risk management. Therefore, investment trading education should also encompass an understanding of risks and how to manage them. It is necessary to learn about risk management, capital management, the use of stop loss, and managing emotions in fluctuating market conditions. A better understanding of the market, analysis, strategies, and risk management can help make more informed trading decisions, potentially increasing profits on investments.